Variability in the Responses of Hepatitis B Virus D-Subgenotypes to Antiviral Therapy: Designing Pan-D-Subgenotypic Reverse Transcriptase Inhibitors - Khatun, Mousumi; Kumar, Krishna; Baidya, Ayana; Mondal, Rajiv Kumar; Baszczyňski, Ondřej; Kalčic, Filip; Banerjee, Soma; Dhali, Gopal Krishna; Das, Kausik; Chowdhury, Abhijit; Janeba, Zlatko; Chakrabarti, Saikat; et al. (Journal of virology, 2022)
Nucleos(t)ide analogues entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are recommended as first-line monotherapies for chronic hepatitis B (CHB). Multiple HBV genotypes/subgenotypes have been described, but their impact on treatment response remains largely elusive. We investigated the effectiveness of ETV/TDF on HBV/D-subgenotypes, D1/D2/D3/D5, studied the structural/functional differences in subgenotype-specific reverse transcriptase (RT) domains of viral polymerase, and identified novel molecules with robust inhibitory activity on various D-subgenotypes. Transfection of Huh7 cells with full-length D1/D2/D3/D5 and in vitro TDF/ETV susceptibility assays demonstrated that D1/D2 had greater susceptibility to TDF/ETV while D3/D5 exhibited poorer response. Additionally, HBV load was substantially reduced in TDF-treated CHB patients carrying D1/D2 but minimally reduced in D3/D5-infected patients. Comparison of RT sequences of D-subgenotypes led to identification of unique subgenotype-specific residues, and molecular modeling/docking/simulation studies depicted differential bindings of TDF/ETV to the active site of their respective RTs. Replacement of signature residues in D3/D5 HBV clones with corresponding amino acids seen in D1/D2 improved their susceptibility to TDF/ETV. Using high throughput virtual screening, we identified N(9)-[3-fluoro-2-(phosphonomethoxy)propyl] (FPMP) derivatives of purine bases, including N6-substituted (S)-FPMP derivative of 2,6-diaminopurine (DAP) (OB-123-VK), as potential binders of RT of different D-subgenotypes. We synthesized (S)-FPMPG prodrugs (FK-381-FEE/FK-381-SEE/FK-382) and tested their effectiveness along with OB-123-VK. Both OB-123-VK and FK-381-FEE exerted similar antiviral activities against all D-subgenotypes, although FK-381-FEE was more potent. Our study highlighted the natural variation in therapeutic response of D1/D2/D3/D5 and emphasized the need for HBV subgenotype determination before treatment. Novel molecules described here could benefit future design/discovery of pan-D-subgenotypic inhibitors. IMPORTANCE Current treatment of chronic hepatitis B relies heavily on nucleotide/nucleoside analogs in particular, tenofovir disoproxil fumarate (TDF) and entecavir (ETV) to keep HBV replication under control and prevent end-stage liver diseases. However, it was unclear whether the therapeutic effects of TDF/ETV differ among patients infected with different HBV genotypes and subgenotypes. HBV genotype D is the most widespread of all HBV genotypes and multiple D-subgenotypes have been described. We here report that different subgenotypes of HBV genotype-D exhibit variable response toward TDF and ETV and this could be attributed to naturally occurring amino acid changes in the reverse transcriptase domain of the subgenotype-specific polymerase. Further, we identified novel molecules and also synthesized prodrugs that are equally effective on different D-subgenotypes and could facilitate management of HBV/D-infected patients irrespective of D-subgenotype.
Keywords: mutace; Antiviral Agents; guanin; hepatitis B virus D-subgenotypes; Genotype; Reverse Transcriptase Inhibitors; Organophosphonates; phosphonate prodrug; inhibitory reverzní transkriptasy; virová nálož; Prodrugs; antivirové látky; Tenofovir; proteinové domény; lidé; RNA-Directed DNA Polymerase; genotyp; Mutation; prekurzory léčiv; Protein Domains; chronická hepatitida B; virová léková rezistence; antiviral activity; organofosfonáty; high throughput virtual screening; Viral Load; racionální návrh léčiv; entecavir; Drug Design; Drug Resistance, Viral; Guanine; tenofovir; Hepatitis B virus; Hepatitis B, Chronic; reverzní transkriptasa; virus hepatitidy B; Humans